Community identity construction: A case study of digital literacy activists in Next Generation Indonesia Community - Jibril Bela Abdillah; Tisna Prabasmoro; Dade Mahzuni (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2025)
Next Generation Indonesia (NXG Indonesia), a community dedicated to enhancing digital literacy, underscores its role as a social actor within the digital literacy discourse. The status of NXG Indonesia as a social actor in this discourse renders discussions about it inherently linked to issues of identity. Consequently, this study aims to elucidate the construction of the identity of the NXG Indonesia community and examine how this identity construction influences the habitus of NXG Indonesia. To achieve these research objectives, a qualitative methodology employing a case study approach was utilized, with data collected through in-depth interviews with five informants who were members of the NXG Indonesia community. The findings indicate that the identity of the NXG Indonesia community is constructed through elements such as locus, distinctiveness, identification, orientation, evaluation of community life, and evaluation of community functioning, all of which have implications for the NXG Indonesia habitus, particularly its commitment to digital literacy. Therefore, this study concludes that social interactions among individuals within NXG Indonesia significantly impact the construction of the community's identity and habitus.   Next Generation Indonesia (NXG Indonesia), sebuah komunitas yang berdedikasi dalam mengupayakan peningkatan literasi digital, menegaskan perannya sebagai aktor sosial dalam wacana literasi digital. Status NXG Indonesia sebagai aktor sosial dalam wacana ini mengakibatkan diskusi mengenai NXG Indonesia tidak dapat dipisahkan terkait dengan masalah identitas. Dengan demikian, penelitian ini bertujuan untuk menjelaskan konstruksi identitas komunitas NXG Indonesia dan melihat bagaimana konstruksi identitas tersebut mempengaruhi habitus dari NXG Indonesia. Untuk mencapai tujuan penelitian tersebut, penelitian ini mengunakan metodologi kualitatif dengan pendekatan studi kasus serta metode pengumpulan data melalui wawancara mendalam bersama dengan lima informan yang tergabung dalam komunitas NXG Indonesia. Hasil penelitian menunjukkan bahwa identitas komunitas NXG Indonesia dikonstruksi melalui elemen-elemen seperti locus, distinctiveness, identification, orientation, evaluation of community of life, dan evaluation of community functioning yang berimplikasi pada habitus NXG Indonesia, khususnya komitmennya terhadap literasi digital. Oleh karena itu, penelitian ini menyimpulkan bahwa interaksi sosial di antara individu-individu di dalam NXG Indonesia secara signifikan memengaruhi konstruksi identitas dan habitus komunitas.